Hospital-Associated Multidrug-Resistant MRSA Lineages Are Trophic to the Ocular Surface and Cause Severe Microbial Keratitis - Paulo J. M. Bispo; Paulo J. M. Bispo; Lawson Ung; Lawson Ung; James Chodosh; James Chodosh; Michael S. Gilmore; Michael S. Gilmore; Michael S. Gilmore (Frontiers in Public Health, 2020)
Methicillin-resistant Staphylococcus aureus (MRSA) is a common cause of severe and difficult to treat ocular infection. In this study, the population structure of 68 ocular MRSA isolates collected at Massachusetts Eye and Ear between January 2014 and June 2016 was assessed. By using a combination of multilocus sequence typing (MLST) analysis, SCCmec typing and detection of the panton-valentine leukocidin (PVL) gene, we found that the population structure of ocular MRSA is composed of lineages with community and hospital origins. As determined by eBURST analysis of MLST data, the ocular MRSA population consisted of 14 different sequence types (STs) that grouped within two predominant clonal complexes: CC8 (47.0%) and CC5 (41.2%). Most CC8 strains were ST8, harbored type IV SCCmec and were positive for the PVL-toxin (93.7%). The CC5 group was divided between strains carrying SCCmec type II (71.4%) and SCCmec type IV (28.6%). Remaining isolates grouped in 6 different clonal complexes with 3 isolates in CC6 and the other clonal complexes being represented by a single isolate. Interestingly, major MRSA CC5 and CC8 lineages were isolated from discrete ocular niches. Orbital and preseptal abscess/cellulitis were predominantly caused by CC8-SCCmec IV PVL-positive strains. In contrast, infections of the cornea, conjunctiva and lacrimal system were associated with the MDR CC5 lineage, particularly as causes of severe infectious keratitis. This niche specialization of MRSA is consistent with a model where CC8-SCCmec IV PVL-positive strains are better adapted to cause infections of the keratinized and soft adnexal eye tissues, whereas MDR CC5 appear to have greater ability in overcoming innate defense mechanisms of the wet epithelium of the ocular surface.